Product-Centered Language Style in Chinese Women Online Reviews - Wang, Xian; Mu, Congjun; Li, Huixian; Noble, Alison; Wang, Qingyi (Frontiers in Psychology, 2022)
The relationship of language style and online review has drawn increasing academic attention recently as it can provide customers with a guide to make purchase. Extant research attaches importance to the language style that is presented in the use of function words, instead of product-related content words. This paper aims to examine the language style generated by customers’ comments relating to the product based on content words, that is, product-centered language style (PCLS). We build a corpus of Chinese women clothes online reviews to explore the general picture and distinct features of PCLS and the distinct feature of PCLS. A content-word-centered Linguistic Inquiry and Word Count (LIWC) in terms of the product performance is established. PCLS is calculated based on the Language Style Matching (LSM) algorithm. Our results show that the PCLS in women clothes online review is diverse and polarized among 3 groups of women clothes buyers, and prioritized arrangement of words of importance contributes to the PCLS. The findings benefit the women clothes industry in that it can help companies find the distinctive and the transition of PCLS, and offers an approach for companies to indiscriminately look into significance of the product category from the linguistic perspective, which can help with product sales strategy and product design.